2022
DOI: 10.1021/acs.inorgchem.2c03487
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene Gold Complexes in a Photocatalytic CO2 Reduction Reaction

Abstract: Molecular catalysts that are durable and highly selective in the photocatalytic CO2 reduction reaction (PCO2RR) are in high demand. Molecular gold complexes are underexplored in the CO2RR manifold despite heterogeneous gold–CO2 reduction catalyst counterparts being frequently studied. In this report, a series of N-heterocyclic carbene (NHC)-ligated Au complexes are evaluated in the PCO2RR with an added photosensitizer (tris(2-phenylpyridine)iridium, Ir(ppy)3). The complexes were each studied with and without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Nugegoda et al reported the first examples of Au-based NHC-ligated molecular catalysts for CO 2 photoreduction. 36 They studied the photocatalytic performances of eleven Au–NHC complexes, which varied in their wingtip substituents, the saturated or unsaturated NHC backbone and the labile ligand (counterion) on the Au center. Among them, the mesitylene wingtip-bearing complex showed the highest TOF of 8.4 h −1 and TON of 45, ascribed to the small wingtip ligand, unsaturated backbone and easily dissociated chloride ligand (Table 1, entry 11).…”
Section: Synthesis Of and Photocatalytic Co2 Reduction By Metal–nhc C...mentioning
confidence: 99%
“…Nugegoda et al reported the first examples of Au-based NHC-ligated molecular catalysts for CO 2 photoreduction. 36 They studied the photocatalytic performances of eleven Au–NHC complexes, which varied in their wingtip substituents, the saturated or unsaturated NHC backbone and the labile ligand (counterion) on the Au center. Among them, the mesitylene wingtip-bearing complex showed the highest TOF of 8.4 h −1 and TON of 45, ascribed to the small wingtip ligand, unsaturated backbone and easily dissociated chloride ligand (Table 1, entry 11).…”
Section: Synthesis Of and Photocatalytic Co2 Reduction By Metal–nhc C...mentioning
confidence: 99%
“…Transition-metal complexes as a kind of molecular catalysts for homogeneous systems have attracted enormous attention due to their clear molecular structures and catalytic active sites, which facilitates the exploration of the relationship between structure and catalytic performance . In recent years, various precious metal (such as Re, Ir, Au, , and Ru , ) complexes have been employed as molecular catalysts for photocatalytic reduction of CO 2 . Although these kind of complexes usually display excellent photocatalytic performance for CO 2 reduction, the development of nonprecious metal (such as Co, Mn, Ni, , and Fe ) complex catalysts has become a hot spot due to the high cost of precious metal complexes.…”
Section: Introductionmentioning
confidence: 99%